Changes in the Folate Content and Fatty Acid Profile in Fermented Milk Produced with Different Starter Cultures during Storage - Marta Czarnowska-Kujawska; Beata Paszczyk (Molecules, 2021)
The application of bacterial cultures in food fermentation is a novel strategy to increase the “natural” levels of bioactive compounds. The unique ability of lactic acid bacteria (LAB) to produce folate, B vitamins, and conjugated linolenic acid cis9trans11 C18:2 (CLA) during cold storage up to 21 days was studied. Although some species of LAB can produce folates and other important nutrients, little is known about the production ability of yogurt starter cultures. Pasteurized milk samples were inoculated with four different combinations of commercially available yogurt vaccines, including starter cultures of Bifidobacterium bifidum. Both the type of vaccine and the time of storage at 8 °C had a significant effect on the folate and CLA contents in the tested fermented milks. The highest folate content (105.4 µg/kg) was found in fresh fermented milk inoculated with Lactobacillus delbrueckii, Streptococcus thermophilus, and Bifidobacterium bifidum. Only the mix of Lactobacillus delbrueckii subsp. bulgaricus, Streptococcus thermophilus, and Bifidobacterium bifidum showed potential (59% increase) to synthesize folate during seven days of storage. A significant increase in the content of CLA, when compared to fresh fermented milk, was observed during cold storage for up to 21 days in products enriched with Bifidobacterium bifidum.